Restorative Justice in the National Criminal Code: An Analysis of Probation and Community Service under Law No. 1 of 2023 - Rabith Madah Khulaili Harsya; Rani Eka Arini; Salwa Aulia Novitasari (West Science Law and Human Rights, 2026)
The enactment of Law No. 1 of 2023 concerning the Indonesian Criminal Code marks a significant transformation in Indonesia’s criminal justice system by introducing probation and community service as principal non-custodial sanctions. These forms of punishment reflect a shift from a predominantly retributive approach toward a more rehabilitative, proportional, and restorative-oriented sentencing policy. This study aims to analyze the legal construction of probation and community service under Law No. 1 of 2023 and to assess their consistency with the principles of restorative justice. The research applies a normative legal method using statutory, conceptual, and comparative approaches. The legal materials consist of Law No. 1 of 2023, Law No. 22 of 2022 concerning Corrections, relevant international instruments, and scholarly literature on restorative justice and non-custodial sanctions. The materials are analyzed qualitatively through descriptive, systematic, and prescriptive legal interpretation. The findings show that probation and community service provide progressive alternatives to short-term imprisonment by supporting offender rehabilitation, maintaining family and employment relationships, reducing prison overcrowding, and encouraging accountability through supervision and socially beneficial work. However, these sanctions do not fully constitute restorative justice mechanisms because victim participation, mediation, restitution, and reconciliation remain limited. Their effectiveness depends on comprehensive implementing regulations, institutional readiness, judicial consistency, qualified supervisory personnel, inter-agency coordination, and community involvement. The study concludes that Law No. 1 of 2023 establishes an important normative foundation for restorative-oriented sentencing in Indonesia, although further institutional and procedural development is required to ensure that probation and community service effectively achieve justice, legal certainty, social benefit, and public protection.